The Use of Technology to Improve the Efficiency of Modern Pharmacy Management - Chairatanaprapa, Pachara; Pakittawichit, Thananchakorn; Sukhaparamate, Supawat (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The modern pharmaceutical business faces rapid changes in an environment where technology plays a key role in the development of products and services. The use of technology in management can help increase efficiency in business processes and strengthen the ability to adapt and adapt to changes occurring in the pharmaceutical industry. This article aims to present guidelines and methods in which modern pharmaceutical businesses can use technology to increase the efficiency of modern pharmacy management in stock management, quality inspection, and product quality assurance. Methodology: This study is a study of related documents and research, analyzed and presented according to the study objectives. Results: To use of technology increases efficiency in the management of modern pharmacies, including inventory management, prescription processing, prescription Processing, Medication Dispensing, Patient Communication, Data Analytics, and Regulatory Adherence. Conclusion: The results indicate that employing technology leads to enhanced efficiency across various aspects of modern pharmacy management. This includes improvements in inventory management, prescription processing, medication dispensing, patient communication, data analytics, and regulatory adherence.